L’électronique à l’aide de l’éditeur : miracle ou mirage ? Bilan de quatorze années de travaux au LFA - Pierre Kunstmann (Perspectives Médiévales)
This article first presents an overview of a fourteen-year study (1997-2011), led at the Laboratoire du Français Ancien (LFA, University of Ottawa). The collected data is available on the website www.lfa.uottawa.ca, which is built in two parts : the ‘‘Textes de Français Ancien’’ database and the series entitled ‘‘Textes en Liberté’’. Several works are the result of a collaboration with the ATIFL (CNRS, Nancy, France), namely the « Base de Graphies Verbales », the « Dictionnaire Électronique de Chrétien de Troyes » and the electronic critical edition of the Miracles de Notre-Dame par personnages. This website also hosts the ARLIMA bibliographical database. Such electronic textual resources have become extremely valuable in an editor’s work. Indeed, the wide range of tools the database offers allows its user to address efficiently a great number of texts.